Review Essay: Landscapes/Voices In/Of Transition/Transformation - Noel Gough (Environmental Association of Southern Africa, 2004)
Krog, Antjie. (2003). A Change of Tongue. Johannesburg: Random House. Pieterse, Edgar, & Meintjies, Frank (Eds). (2004). Voices of the Transition: The Politics, Poetics and Practices of Social Change in South Africa. Sandown: Heinemann.